Keeping Track of the Genealogy of Heterozygotes Using Epigenetic Reference Codes and Breeding Tables - Liberati, Anna Sara; Calcaprina, Barbara; Adriani, Walter (Frontiers in Behavioral Neuroscience, 2022)
The accurate and efficient monitoring of the genealogy of heterozygous animal specimen, on which observations are carried on with the purpose of studying their pedigree line, is undoubtedly an operation of great importance in order to keep correct track of the origins and characteristics of each epi-genotype. This not only allows to organize and quickly find all the information related to the different types of specimens, especially heterozygote ones, on which working on but also to label each of them with a coherent and simple abbreviation. This enables immediate identification, thus avoiding the understandable confusion that can arise, especially when working on many different types of specimens obtained from multiple hybridizations. Here we would like to illustrate our own pedigree table, which was specifically designed with the aim of having at hand all the information relating to the main characteristics of the different strains of specimens under study, simply through an optimized use of the nominative abbreviations that identify each one of them.